Exploring Health Experts' and Creative Communicators' Focus in Pandemic Video Communication: A Qualitative Study - Shortt, Marie Therese; Berg, Siv Hilde; Wiig, Siri; Lungu, Daniel Adrian; Smeets, Ionica; Thune, Henriette; Røislien, Jo (Frontiers in Communication, 2022)
Pandemic video communication aimed at the general public often lacks in creativity and fails to reach large audiences. Yet, the scientific content should not be compromised by attempts to improve creativity or reach. This study explores the processes utilised by various health experts and professional communicators when creating communication, to identify similarities and differences, and how pandemic video communication thus can be improved through interdisciplinary approach. We interviewed twelve individuals from six different professional domains: health, public health, film/science communication, video journalism, advertising, and social media/YouTube. Semi-structured individual interviews were conducted using the same interview guide. The interview data was subjected to thematic analysis with both deductive and inductive coding, and results were visualised in a bubble chart. Our study has highlighted both similarities and differences between health professionals and creative communicators relating to their creative processes, and to their approaches to pandemic video communication. We found that participants from health domains assigned great importance to and effort on content, but were unsure or lacked experience in how content is translated through form and creativity. Creative communicators, on the other hand, emphasise and specialise in form, yet depend on health professionals, experts, and scientists to provide and validate content. Key to improving pandemic related video communication appears to lie in striking the right balance between high-quality and evidence-based content and creativity. This study found that both health professionals and creative communicators play crucial roles in reaching a solid end result, and we suggest a fusion model approach to interdisciplinary collaboration.